La revocatoria definitiva de la licencia de conducir y la vulnerabilidad del derecho al trabajo, en los delitos culposos de tránsito - Ortiz Farfán, Maritza Elizabeth (2016)
Art. 376 of the Code Integral Penal says that the person who drives a motor vehicle while intoxicated or under the influence of narcotics, psychotropic substances or preparations containing substances and cause a traffic accident resulting dead one or more persons, shall be punished with imprisonment of ten to twelve years, final revocation of the license to drive vehicles. An end of the driver's license revoked for this offense is a perpetual penalty, for if the accused and the accused and paid to society culpable offense with imprisonment up to twelve years, there is no legal basis for the legislature established partially in this provision a perpetual penalty, being unequal in context, affecting the civil rights of the accused, mentioned in Art. 66 paragraph 15 of the Constitution of the Republic of Ecuador, such as the right to engage in economic activities, in the form individually or collectively, in accordance with the principles of solidarity, responsibility and environmental; and the indicated in paragraph 17 of Art. 66 of the same constitutional provision, the right to freedom of work. In addition many people leave serves as financial support exists, and being convicted of culpable does not imply that life is denied the right to drive a motor after serving the sentence imposed by the court or judge corresponding. The final revocation of driver's license is an exclusive sanction indicated in Art. 376 of the Code Integral Criminal, for the crime of death caused by the driver intoxicated or under the influence of narcotics, psychotropic substances or preparations that contain, with the final repeal a non-custodial sentence, and compared to those mentioned in Art. 60 of the same Act, there is no such legal concept, and pigeonholed penalties for traffic offenses concerning the license driving, we have the suspension of the authorization or license to drive any type of vehicle and loss of points on your driver's license, being the ultimate driver's license to a penalty which has no legal legality revocation. In this case and the principle of legality, on the basis of Art. 60 of the Code Integral Penal, that by not stated in this provision the definitive driver's license revoked, it is best to discontinue use of the license for the same duration of the sentence also violates the purpose of punishment, which is between the other progressive development of the rights and capacities dela person with conviction, and with the penalty of definitive revocation of the license to the person is neutralized as a social being. The final revocation of driver's license in the case of culpable traffic offenses, lack of legality in it, as Art says. 53 of the Code Integral Criminal no more severe penalties will be imposed than those determined in the criminal of this Code. The duration of the sentence must be determined. Indefinite penalties are proscribed. This affects the right to work on a person and therefore goes against Art. 11, paragraph 4 of the Constitution of the Republic of Ecuador, that no legal rule may restrict the content of the rights and constitutional guarantees, affecting legal certainty guaranteed in Art. 82 of the constitutional provision that rules should be clear, before and applicable to the competent authorities. And according to Art. 100 of the Organic Law of Land Transport, Traffic and Road Safety, says that will be revoked the license when you come upon obstacles, incapacitating physical, mental or legally its holder to drive, lacking in the law to revoke final, and bases that this violates the rights of people prosecuted and sentenced.